Gambaran Kebahagiaan pada Anggota Kepolisian Satintelkam Polresta Surakarta - Ella Putri Febria (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Happiness of police officers is an important aspect that affects their performance and effectiveness in carrying out their duties. This study aims to gain an understanding & examine in depth the description of happiness of Satintelkam police members. This research uses a qualitative approach. There were seven participants with the criteria of police members of Satintelkam Polresta Surakarta. Interviews and observations were used as data collection methods. The results showed that happiness is obtained when making a positive contribution to others, having harmonious relationships with colleagues, and living life with gratitude and a spirit of service. Happiness of SatIntelkam police members is also influenced by involvement in work and good relationships with the work environment.